Leader Role in Shaping Organization Values in Crisis - D. E. Styurina (Вестник Российского экономического университета имени Г. В. Плеханова)
Today’s economic situation causes uncertainty in the majority of companies. In spite of numerous difficulties companies shall be flexible, responsive to customer requests that grow in number from day to day. As a result such companies win competition. Leaders, who can introduce innovation strategies, also possess considerable advantage. Strategy implies not only planning of steps aimed at taking a market share or developing a new product. It is not enough just to calculate the project economics. Such components as introduction of necessary corporate culture, social responsibility of the company, building a strong team are very important. A key advantage in this situation is correctly introduced system of organizational values. Today’s generation plays serious attention to social and psychological climate and corporate values that underlie the business. In future companies that built a strong social mission will possess one of the leading HR brands. The article studies the essence and provides classification of obligatory types of values, investigates the process of managing the system of organization values and shows interaction of the value system of individual, organization and society.